The Digital Phlebotomist: Can AI Analyze Blood Test Results with Clinical Accuracy? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The Digital Phlebotomist: Can AI Analyze Blood Test Results with Clinical Accuracy? The New Frontier of Diagnostics The routine blood test is arguably t...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care